2023
DOI: 10.1002/adma.202304256
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Interphase Dissolution Via Solvent Molecule Tuning for Sodium Metal Batteries

Abstract: Solvent molecule tuning is used to alter redox potentials of solvents or ion‐solvent binding energy for high‐voltage or low‐temperature electrolyte. Herein, we propose an electrolyte design strategy that effectively suppresses solid electrolyte interphase (SEI) dissolution and passivates highly‐reactive metallic Na anode via solvent molecule tuning. With rationally lengthened phosphate backbones with –CH2– units, the low‐solvation tris(2‐ethylhexyl) phosphate (TOP) molecule effectively weakens the solvation ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Remarkably, NVP∥ZMOF-NSC@Na batteries exhibited a sustained specific capacity of 79.91 mAh g –1 after 2000 cycles at 10 C, with an exemplary average CE of 99.86% and minimized polarization, as detailed in Figure c, which demonstrates that ZMOF-NSC exhibits excellent protection of the anode. Nevertheless, under the same conditions, the NVP∥bare Na batteries observed a rapidly increasing charge/discharge polarization (Figure a,d), showing extremely poor cycling stability due to the severe side reactions and dendrite formation . At an elevated current density of 20 C, as shown in Figure b, NVP∥ZMOF-NSC@Na batteries astonishingly demonstrated a stable cycling performance over 3000 cycles, in contrast to the rapid capacity fade observed in bare Na, which can be attributed to the fast Na + transport improved by ZMOF-NSC.…”
Section: Resultsmentioning
confidence: 85%
“…Remarkably, NVP∥ZMOF-NSC@Na batteries exhibited a sustained specific capacity of 79.91 mAh g –1 after 2000 cycles at 10 C, with an exemplary average CE of 99.86% and minimized polarization, as detailed in Figure c, which demonstrates that ZMOF-NSC exhibits excellent protection of the anode. Nevertheless, under the same conditions, the NVP∥bare Na batteries observed a rapidly increasing charge/discharge polarization (Figure a,d), showing extremely poor cycling stability due to the severe side reactions and dendrite formation . At an elevated current density of 20 C, as shown in Figure b, NVP∥ZMOF-NSC@Na batteries astonishingly demonstrated a stable cycling performance over 3000 cycles, in contrast to the rapid capacity fade observed in bare Na, which can be attributed to the fast Na + transport improved by ZMOF-NSC.…”
Section: Resultsmentioning
confidence: 85%
“…The electrolyte, as a crucial component of SIBs, is closely related to the formation of EEI. , Numerous researchers demonstrated that electrolyte design is an effective strategy for constructing a robust NaF-rich EEI, including high-concentration electrolyte, localized high-concentration electrolyte, , all fluorinated electrolyte, , etc. However, the practical application of these electrolyte systems is limited by their expensive cost.…”
mentioning
confidence: 99%